2004
DOI: 10.1023/b:neab.0000028286.83083.73
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Behavior and Stress-Reactivity of the Hypophyseal-Adrenal System in Prenatally Stressed Rats

Abstract: The effects of daily 1-h immobilization of female rats from days 15 to 18 of pregnancy on the levels of anxiety, orientational-investigative activity in an open field test, and the dynamics of the stress response of the hypophyseal-adrenal system were studied in the male and female adult offspring of these rats. Maternal stress was found to induce significant reductions in the level of orientational-investigative activity of females in the stage of diestrus, and to increase anxiety as measured in an elevated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
1
6
0
8
Order By: Relevance
“…This suggests that prenatal stress may alter the sensitivity of hippocampal receptors to estradiol or other neuroactive steroids. Irrespective of the stage of the estrous cycle, prenatal stress abolished the difference in anxiogenic behavior in the two sexes as shown in other studies (Fride and Weinstock, 1988;Ordyan and Pivina, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…This suggests that prenatal stress may alter the sensitivity of hippocampal receptors to estradiol or other neuroactive steroids. Irrespective of the stage of the estrous cycle, prenatal stress abolished the difference in anxiogenic behavior in the two sexes as shown in other studies (Fride and Weinstock, 1988;Ordyan and Pivina, 2004).…”
Section: Discussionsupporting
confidence: 75%
“…A reciprocal relationship between pharmacological addiction and HPA activation may exist, such that stress and HPA activation promote the likelihood of use (Goeders 1997, 2002ab), and use alters HPA arousal. Indeed, research in animal models indicates that early stress experiences alter HPA response throughout life such that HPA hormones can be down-regulated while ligand targets can be upregulated and these effects are sex-dependent with males attenuating and females hyper-activating HPA response (Bosch et al, 2007; Mabandla et al, 2007; Ordyan and Pivina, 2004). As well, reinforcing properties of hedonic stimuli can be enhanced by early stress (Kippin et al, 2007).…”
Section: Stress Response and Engagement In Gambling Behavior In The Nmentioning
confidence: 99%
“…Indeed, it was shown in a number of studies that prenatal stress induces high anxiety in offspring as revealed by tests including the EPM, open field, and social interaction in rats (e.g. Vallee et al, 1997;Estanislau and Morato, 2005) and mice (Chung et al, 2005), while only a few studies have found no effect (Ordyan and Pivina, 2004). The early postnatal period and the bond between mother and infant seems particularly important in the development and shaping of normal emotional behavior (for recent reviews see Holmes et al, 2005;Pryce et al, 2005).…”
Section: Stress-based Models Of Enduring Anxietymentioning
confidence: 99%